A Study of Human Resource Management in Iranian Oraganizations- Opportunities for Learning - Asl, Samad Jabbari (Gyan Management Journal, 2008)
Con idering the abov , a learning organization can be described as an organization which responds to (and anticipat s) changes in its environment by learning on a strategic level. Mor over, it deliberately aim at improving its ability to learn by single loop and double loop learning. It make us of the learning of all employees; therefore this employee learning is nhanced at all hierarchical levels (Argyri & chon, 1978). Organizations that focus on creating opportuniti s for mployee learning, with the longterm goal of b coming a learning organization, can be lab led 'learning riented organizations . eys et al. (1992) describ them as organizations which creal {on-thejob as well as off-th -job) facilities for employee 1 arning. Moreover these organizations stimulate employees not only to attain new knowl dge and kills, but also to acquire skills in th field ofl arning and problem solving and thus d velop th ir capacity for future  arning (Tjepk ma & Wognum, UW6). One ould say that becoming a learning oriented organization is the first stag in the growth proce s towards a learning organization.
Keywords: Human Resource; Iranian Oraganizations; environment